3D thermoelastoplastic study of FML structure under the action of a moving Gaussian-distributed laser heat source. (October 2022) - Jiang, Hao-Jie; Xu, Wen-Lei; Gao, Ning-Hua; Jia, Chun-Song; Wang, Xiao-Gui
Abstract: Fiber metal laminated (FML) structures are used widely, however, studies on the three-dimensional thermoelastoplastic behaviors of FML structure subjected to a moving Gaussian-distributed laser heat source have not yet been developed. In present work, the semi-analytical solution of three-dimensional transient heat transfer equation for FML structure under the action of a moving Gaussian-distributed laser heat source is obtained through the separate variable method (SVM) and the Newton Cotes method (NCM). A yield criterion related to spherical tensor of stress is proposed to describe the mixed hardening of the orthotropic FML structure. Based on classical nonlinear laminated plate theory, the incremental nonlinear governing equations are obtained, and the equations are solved by the combination of finite difference method, Newmark method and iterative method. Numerical results show that the temperature field, moving velocity of laser, number of FML layers, thickness ratio and boundary condition have great influences on thermoelastoplastic behaviors of the FML structure. Graphical abstract: Highlights: Laser moving velocity affects the temperature field, and influences both the equivalent elastoplastic coefficients and strain increments together subsequently. More alternate layer could resist great deformation although both of two with the same fiber/metal ratio along the height. Increase of equivalent elastoplastic coefficients play the dominant role than decrease of strains for fixed FML structure.